Authority and Responsibility of Local Government in Managing Environmental Pollution Impact of PT Lotte Chemical Project in Cilegon City - Rizka Deviana Putri; Rokilah Rokilah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the authority and responsibility of the local government, particularly the Environmental Agency (DLH) of Cilegon City, in managing the environmental impacts of the PT Lotte Chemical project. The research adopts an empirical legal approach with a socio-legal perspective by combining document analysis of Environmental Impact Assessment (AMDAL) and interviews with DLH officials. Findings show that the distribution of authority in environmental management refers to Law No. 32 of 2009 and Law No. 23 of 2014, which allocate responsibilities between central, provincial, and local governments. However, the implementation by DLH Cilegon encounters obstacles due to limited authority in sanctioning and dependency on the Ministry of Environment and Forestry (KLHK). In terms of responsibility, DLH tends to take a permissive stance, considering the project is still under construction and contributes to economic growth, which affects the effectiveness of environmental supervision. This study highlights the gap between legal provisions and practical enforcement, suggesting the need for stronger local capacity and better coordination with the central government.